1989
DOI: 10.1210/endo-124-2-762
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Development of the Adult Population of Leydig Cells in Testes of the Pubertal Rat*

Abstract: The objective of this study was to determine whether postnatal increases in rat Leydig cell number result from differentiation of precursor cells, division of existing Leydig cells, or both. Our approach was 1) to examine changes in the absolute number of Leydig cells and potential precursor cells (macrophages, pericytes, and mesenchymal, endothelial, and myoid cells) per testis on day 19 of gestation (day -2) and days 7, 14, 21, 28, and 56 postpartum; 2) to examine the frequency with which mesenchymal and Ley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
176
2
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(192 citation statements)
references
References 25 publications
(19 reference statements)
12
176
2
2
Order By: Relevance
“…This observation is also in full agreement with the estimate of total Leydig cell numbers per testis, as well as with the secretion profiles for the peptide hormone INSL3. Leydig cell numbers were close to those previously reported by Zirkin and Ewing 31 and Hardy et al 17 Close inspection of the testicular histology (data not shown) indicated that the increase in Leydig cell numbers did not appear to be associated with any kind of focal hyperplasia as has been reported for the fetal testis under DBP treatment. 32 Nor was there any evidence for focal atrophy in any of the testes examined, which, however, did exclude any of the grossly dysgenic testes resulting from maternal DBP treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This observation is also in full agreement with the estimate of total Leydig cell numbers per testis, as well as with the secretion profiles for the peptide hormone INSL3. Leydig cell numbers were close to those previously reported by Zirkin and Ewing 31 and Hardy et al 17 Close inspection of the testicular histology (data not shown) indicated that the increase in Leydig cell numbers did not appear to be associated with any kind of focal hyperplasia as has been reported for the fetal testis under DBP treatment. 32 Nor was there any evidence for focal atrophy in any of the testes examined, which, however, did exclude any of the grossly dysgenic testes resulting from maternal DBP treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Microscope images were captured on Spot analysis software (Diagnostic Instruments Inc., Sterling Heights, MI, USA) using a 3100 oil-free Figure 1 Diagram to illustrate the treatment and sampling regimen applied (small dots above the bar indicate approximate blood sampling times). The morphological changes during pubertal Leydig cell differentiation (after [16][17][18] ) are illustrated at their corresponding times in the upper section of the figure. GD, gestational day; PND, postnatal day; DBP, dibutyl phthalate; DES, diethylstilbestrol.…”
Section: Leydig Cell Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitotic activity of PLCs gradually is reduced, and the cells enlarge in transition to another intermediate, the immature LC (ILC), during days 28-56 postpartum. ILCs undergo a final division and transform into testosterone-secreting adult LCs (ALCs) by day 56 (10).…”
mentioning
confidence: 99%
“…In the prepubertal animal, mesenchymal cells represent the largest interstitial cell population. With the onset of puberty, their relative number decreases whereas LC number increases to become the most abundant interstitial cell type in the mature animal (Hardy et al, 1989;Vergoween et al, 1993).…”
mentioning
confidence: 99%